Catholic Identity in Practice: A Survey on Awareness and Understanding of the Basic Catechism Among College Students - Margelyn L. Goaynon; Jomar Troy P. Abregana; Ermito R. Dayaba; Christine Faith G. Marpa; Ivan D. Tata; Shane Dee C. Tinanyag; Benedict L. Angco Jr; Evan P. Taja-on (PT FORMOSA CENDEKIA GLOBAL, 2026)
Many young Catholics actively participate in religious practices, yet their understanding of the deeper meaning of these actions often remains limited. This disconnects between spiritual practice and doctrinal knowledge highlights the importance of strengthening catechetical formation. Strengthening catechetical formation among college students is vital for nurturing deeper spiritual growth, moral integrity, and a stronger sense of belonging within the Church. The research gathered data from college students using a structured questionnaire, with respondents drawn proportionally from different academic departments. The findings reveal that college students show strong awareness of Catholic teachings, especially in daily life and moral actions, but their understanding remains largely basic in areas related to belief, worship, and faith identity. This gap suggests that while faith is recognized and practiced, deeper comprehension of its meaning requires further formation. The results emphasize the importance of strengthening catechetical formation among college students to bridge the gap between awareness and understanding of the basic teachings of the Catechism.